WEBGIS APPLICATION FOR SEARCHING THE NEAREST CAR AC REPAIR SERVICE IN METRO CITY USING THE VINCENTY ALGORITHM - Rayhan Prasetiyo; Budi Sutomo (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
The rapid increase in vehicle mobility in Metro City has led to a higher demand for specialized car AC maintenance services. This study develops a WebGIS-based application designed to facilitate the search for the nearest car AC workshops by implementing the Vincenty Algorithm. Unlike standard digital maps that often use spherical models, this system utilizes the WGS-84 ellipsoid reference to ensure high precision in geodesic distance calculations. The software was developed using the Waterfall model, integrating PHP, MySQL, and the Leaflet.js library. System validation was conducted through Black Box Testing across seven core modules, achieving a 100% functional validity rate. Comparative analysis between manual Vincenty calculations and system driving distance showed a minimal margin of 0.13 KM or 1.8%, confirming the algorithm's reliability for nearest-location ranking. This WebGIS serves as an efficient digital navigation tool to support vehicle maintenance for the community in Metro City.